Stewart-Treves syndrome - case report and review of the literature - Marta Koper; Agnieszka B. Serwin; Bożena Zdrodowska-Stefanow; Iwona Flisiak (Termedia Publishing House, 2014)
Introduction . Chronic lymphedema, mainly due to total mastectomy with axillary lymph nodes dissection for breast cancer, can induce development of rare and highly malignant cutaneous angiosarcoma. This condition is called Stewart-Treves syndrome (STS). There are only about 400 cases of STS reported in the literature. The long-term prognosis is poor; 5-year survival is up to 10%. Limb amputation appears to be the treatment of choice. Objective . To present a case of Stewart-Treves syndrome with a fatal outcome, which developed 12 years after mastectomy with lymphadenectomy. Case report . A 65-year-old woman was admitted to our department for confluent purpuric macules, hemorrhagic blisters, and violaceous-black nodules, involving the whole left arm and forearm, with chronic severe lymphedema of the extremity. She had a history of left-sided breast cancer 12 years previously, treated with mastectomy with excision of axillary lymph nodes; subsequently, the failure of lymph drainage and lymph stasis developed. Histopathological examination of the tumor was consistent with angiosarcoma. The patient was disqualified from a surgical procedure due to the late stage of malignancy and died approximately a month later. Conclusions . Given unsatisfactory treatment options, the prevention of long-lasting lymphedema is crucial to improve prognosis of patients with breast cancer.